Exosome secretion promotes chemotaxis of cancer cells. Issue 2 (4th March 2017) - Sung, Bong Hwan; Weaver, Alissa M.
ABSTRACT: Migration of cells toward chemical cues, or chemotaxis, is important for many biologic processes such as immune defense, wound healing and cancer metastasis. Although chemotaxis is thought to occur in cancer cells, it is less well characterized than chemotaxis of professional immune cells such as neutrophils. Here, we show that cancer cell chemotaxis relies on secretion of exosome-type extracellular vesicles. Migration of fibrosarcoma cells toward a gradient of exosome-depleted serum was diminished by knockdown of the exosome secretion regulator Rab27a. Rescue experiments in which chemotaxis chambers were coated with purified extracellular vesicles demonstrate that exosomes but not microvesicles affect both speed and directionality of migrating cells. Chamber coating with purified fibronectin and fibronectin-depleted exosomes demonstrates that the exosome cargo fibronectin promotes cell speed but cannot account for the role of exosomes in promoting directionality of fibrosarcoma cell movement during chemotaxis. These experiments indicate that exosomes contain multiple motility-promoting cargoes that contribute to different aspects of cell motility.